Penentuan Kondisi Operasi Optimum Ekstraksi Pewarna Alami Dari Limbah Serbuk Kayu Ulin (Eusideroxylon zwageri) Menggunakan Response Surface Method - Putribarafike, Apriliantina; Rahayuningsih, Edia; Faridah, Eny (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The use of natural dyes is an alternative to replace synthetic dyes. One of the natural resources in Indonesia that can be used as a natural dye is wood sawdust of Ulin wood. Phytochemical analysis results showed that the extract of Ulin wood sawdust contains tannin compound, as the chemical of these sawdust is potential as a source of natural dyes. This research is to find the optimum condition of natural dye extraction from Ulin wood sawdust.  Variables observed in this research are temperature, the weight ratio of sawdust to the solvent volume, and mixer rotation speed. The extraction process with a third necked flask with a stirrer, condenser, heat mantle, and with water as solvents. Natural dye content on the extract was analyzed by gravimetry. The optimization of operating variables extraction using Response Surface Method (RSM) with Box-Behnken model. The results that the optimum temperature was 90oC, the weight ratio of Ulin wood sawdust to the solvent volume was 0,25 g/mL, and the optimum mixer rotation speed was 250 rpm. In this optimum condition, the natural dye content in the extracts was 1,2054%